M. Paz López-Peláez Casellas (coord.). Músicas encontradas. Feminismo, género y queeridad. Jaén. Editorial Universidad de Jaén, 2021.195 pp. (El oído pensante, 2024)
Book review: M. Paz López-Peláez Casellas (coord.) Músicas encontradas. Feminismo, género y queeridad. Jaén. Editorial Universidad de Jaén, 2021.195 pp. ISBN: 978-84-9159-450-5.